Primary pulmonary leiomyosarcoma with invasion of the pulmonary vein—A case report. (2016) - Colwell, Elizabeth M.; Algahim, Mohamed F.; Rao, Arjun; Gasparri, Mario G.
Highlights: Primary pulmonary leiomyosarcomas are rare, less than 0.5% of the organ's primary malignant tumors. Diagnosis of lung tumors at times can be very difficult requiring invasive measures for definitive diagnosis. The mainstay of treatment for leiomyosarcomas is complete surgical resection. However, chemotherapy and radiation can be helpful adjuncts. Abstract: Introduction: Primary pulmonary leiomyosacromas are a subset of the rare sarcomatous lung neoplasms, found to be less than 0.5% of the organ's primary malignant tumors (Attanoos et al., 1996). Presentation of case: We describe here a case of a 69-year-old woman who presented with heart palpitations, incidentally found to have a large lung mass abutting the left inferior pulmonary veins. Challenging tissue diagnosis led to invasive alternatives; attempted full neoplastic resection and pneumonectomy. Discussion: The mainstay of treatment for these tumors is complete surgical resection. Chemotherapy and radiation can be helpful adjuncts as well. Conclusion: This case presents a unique invasion pattern of a primary leiomyosarcoma of the lung, our diagnostic process, and surgical intervention.